A escola técnica do programa Brasil profissionalizado: um projeto padrão para diferentes zonas bioclimáticas? - Lamenha, Melyna de Almeida (2016)
The architectural design becomes a challenge when considering the climate variables. Some of them act directly on users thermal comfort, such as temperature, humidity wind speed and solar radiation. Knowing that different regions may have different climatic conditions and that architecture should be designed according to the climate characteristics, the use of a standard architectural design for the whole country seems an inappropriate choice, particularly in the Brazilian context. The direct incidence of sunlight through windows can cause visual discomfort resulting from blurring, and/or thermal discomfort in warm climates. On the other hand, excessively shaded openings may produce dark spaces, increasing electricity consumption for lighting. Especially in classrooms, visual and/or thermal discomfort may interfere in the learning process and affecting students performance. The Standard Design of the Technical School of MEC - SDTS-MEC is part of Brazil professionalization program and is designed to be deployed throughout the Brazilian territory. This paper evaluates the shading and natural ventilation performance of the teaching/administrative block of SDTS-MEC building, which concentrates the most occupied environments, the classrooms. A characterization the object of study and parametric analysis of shading and natural ventilation were carried on. For the shading analysis, six different locations and eight guidelines were considered. For the analysis of natural ventilation, eight models were considered, each under a different wind incidence. The analysis of the shading devices showed that 15% are appropriate, 9% excessive and 76% insufficient. The results of natural ventilation analysis showed that among eight simulated wind incidences, two of them (with 45° incidence) displayed a higher pressure differential between opposite facades of the teaching/administrative block. These facades contain most apertures, representing greater potential for air movement inside the classrooms. It was observed that the PET-MEC requires adjustments to be deployed. The adjustment simple in sun protection angle of the brizes, and the choice of the most appropriate guidance in relation to solar radiation and prevailing winds, can improve the thermal performance of the project. Finally, a framework containing a set of recommendations for the implantation of the project considering the sunlight and natural ventilation performance were presented.